Information Security Practice and Experience 9th International Conference, ISPEC 2013, Lanzhou, China, May 12-14, 2013. Proceedings - Deng, Robert H.; Feng, Tao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 9th International Conference on Information Security Practice and Experience, ISPEC 2013, held in Lanzhou, China, in May 2013. The 27 revised full papers presented were carefully reviewed and selected from 71 submissions. The papers are organized in topical sections on network security; identity-based cryptography; cryptographic primitives; security protocols; system security; software security and DRM; and cryptanalysis and side channel attacks.
Enhancing False Alarm Reduction Using Pool-based Active Learning in Network Intrusion Detection -- Trusted Identity Management for Overlay Networks -- Situational Awareness for Improving Network Resilience Management -- Optimal Defense Strategies for DDoS defender using Bayesian Game Model -- Identity-Based Cryptography -- Attribute Specified Identity-Based Encryption -- Leakage-resilient Attribute-based Encryption with Fast Decryption: Models, Analysis and Constructions -- Identity-based Multisignature with Message Recovery -- Improving the Message-ciphertext Rate of Lewko's Fully Secure IBE Scheme -- Cryptographic Primitives Accountable Trapdoor Sanitizable Signatures -- A Conditional Proxy Broadcast Re-Encryption Scheme Supporting Timed-Release -- About Hash into Montgomery Form Elliptic Curves -- Secure RFID Ownership Transfer Protocols -- Leakage Resilient Authenticated Key Exchange Secure in The Auxiliary Input Model -- Expressing User Access Authorization Exceptions in Conventional Role-based Access Control -- Cryptanalysis of the OKH Authenticated Encryption Scheme.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Information Systems; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems